Detection of Synchronous Gastric Schwannoma on FDG PET/CT Aided by Discordant Metabolic Response. (May 2015) - Yap, June; Huang, Yi-Tung Tom; Lin, Michael
<x xml:space="preserve">Abstract</x> Abstract This is a case of an unsuspected synchronous gastric schwannoma demonstrating increased 18F-FDG accumulation on PET/CT in a 65-year-old female patient diagnosed with non-Hodgkin lymphoma on the basis of different metabolic activity to other sites of disease at staging and discordant metabolic response to therapy. The gastric schwannoma was confirmed by histopathology and immunohistochemistry after surgical resection. This case adds to the limited literature on FDG-avid gastric schwannoma and highlights the importance of investigating differential metabolic activity and response on serial PET/CT imaging.